Aktivitas Fotodegradasi Fenol Dengan Variasi Suhu Degradasi Menggunakan Komposit Tio2-Cnt(Cocopas) - Nadhia Gasani Putri; Desi Heltina; Panca Setia Utama (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2020)
Phenols found in the wastewater of some industries have acute toxicity. The photocatalysis process can be used to degrade organic compounds such as phenols. To increase the photocatalytic activity of TiO2, a composite formation was formed between TiO2 and carbon nanotubes (CNT). Before being composited, CNT dispersion was carried out using cocoPAS surfactant as dispersing agent. The purpose of this study is to determine the effect of degradation temperature on phenol degradation. The process of making TiO2-CNT(cocoPAS) composites begins by dispersing CNT with cocoPAS surfactants and then composite with TiO2. Photocatalytic activity of the TiO2-CNT(cocoPAS) composite was tested at an initial phenol concentration of 30 ppm with variation of degradation temperature of 30,40 and 50ºC for 4 hours under UV light. Morphology of TiO2-CNT(cocoPAS) composites were characterized using SEM and phenol concentrations were characterized using a UV-Vis spectrophotometer. The highest degradation of phenols by TiO2-CNT(cocoPAS) composites at the initial phenol concentration of 30 ppm was at the degradation temperature of 50ºC, which was 35.59%.Keywords : photocatalysis, composite, TiO2, CNT, cocoPAS, phenol, temperature